AGRIBUSINESS CLINIC PLANNING STRATEGY IN JOMBANG REGENCY - Suci, Ririn Kurnia; Sumarji, Sumarji; Supriyono, Supriyono; Daroini, Ahsin (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Agribusiness clinics are institutions that act as suppliers of agricultural technology innovations so that they are more easily disseminated to farmers and business owners as end users. The concept of clinical agribusiness has been present in Jombang Regency in 2008 as part of Primatani. Currently, the Department of Agriculture has re-launched the agribusiness clinic as the main program in agricultural development in Jombang in 2022. The purpose of this research is to describe the transformation from the old agribusiness clinic concept to a new agribusiness clinic concept, find external and internal environmental support systems in implementing agribusiness clinics in Jombang, and knowing the right strategic planning in the implementation of agribusiness clinics in Jombang Regency. This research is ascriptive qualitative research (level of explanation). Data analysis used is qualitative analysis to describe the transformation of the old concept of agrobusiness clinic to new a concept. Analysis of EFE, IFE, SWOT matrix, IE matrix, and QSPM to determine external and internal environmental system support for clinical agribusiness implementation in Jombang and to find out the right agribusiness planning strategy clinic activities in Jombang. The results of this study are the agribusiness clinic in Jombang has undergone a transformation from the old concept in 2008 to a new concept in 2022. The new concept is the development of the old concept which has undergone adjustments due to changes affecting the agricultural sector. The main external environment support system in the implementation of agribusiness clinics in Jombang Regency the need for healthy and quality agricultural products is increasing. While the main support system of the internal environment is the existence of an extension institution at the district level, namely UPT Implementing Agricultural Extension, and efforts to increase the capacity of farmers and extension workers. The right planning strategy for implementing an agribusiness clinic in Jombang is an Strategy which means utilizing strengths to gain opportunities, namely through strengthening the duties and functions of BPP as the center for implementing agribusiness clinics.